(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
During the Qajar dynasty (1779–1955), Ta’zieh – the epic performance of religious narratives – presented a historical opportunity for Iranian women to transcend patriarchal structures and expand their societal roles through engagement with religious myths. This article explores how Ta’zieh enabled the formation of a unique female identity, demonstrating how women utilized religious frameworks to challenge and overcome restrictions by participating in these epic performances. The focus is on key indicators that facilitated women’s entry into theater and the broader impact these efforts had on their lives.